1983
DOI: 10.1128/iai.40.2.691-695.1983
|View full text |Cite
|
Sign up to set email alerts
|

Response of mouse intestinal loop to botulinum C2 toxin: enterotoxic activity induced by cooperation of nonlinked protein components

Abstract: Botulinum C2 toxin, which is composed of two nonlinked protein components, components I and II, induced fluid accumulation in mouse intestinal loops. The secretory response to C2 toxin was initiated after a lag period of 1 to 2 h and increased gradually for at least 10 h. The activity of C2 toxin was enhanced by treatment with trypsin and abolished by neutralization with anti-component I or anti-component II sera. Neither component I nor component II alone induced the fluid accumulation in intestinal loops. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
4

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 19 publications
2
30
0
4
Order By: Relevance
“…Unlike diphtheria toxin and P. aeruginosa exotoxin, it does not typically cause cell death. The botulinum binary toxin superficially mimics cholera toxin and related substances, because it does promote the movement of fluids across membranes (11,19,20,25), but an action of this toxin on nucleotide-binding proteins has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike diphtheria toxin and P. aeruginosa exotoxin, it does not typically cause cell death. The botulinum binary toxin superficially mimics cholera toxin and related substances, because it does promote the movement of fluids across membranes (11,19,20,25), but an action of this toxin on nucleotide-binding proteins has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Iota toxin appears to share certain properties with the botulinum binary toxin, including the ability to promote the movement of fluids across membranes (5,11,19,20,24). There are also the obvious similarities that both toxins are * Corresponding author.…”
mentioning
confidence: 99%
“…On the other hand, C. botulinum and C. spiroforme have been reported to produce binary toxins (consisting of light and heavy chain components), each of which is similar in molecular weight and action (11,12,14,15). It has been reported that these light chain components ADP-ribosylate synthetic substrates such as homo-poly-L-arginine and actin-like proteins in platelets (12,13), and that the heavy chain component of C. botulinum C2 toxin is responsible for binding of the light chain component to the eucaryotic cells surface (4,(6)(7)(8). On the other hand, little is known about the relationship, between Ia and I, components in lethality and dermonecrosis caused by iota toxin.…”
mentioning
confidence: 99%
“…These results indicate that even when the two components of C2T are incubated separately, component I binds to the cell surface bound with T-II and is processed together with T-II during internalization, as was observed with cells exposed simultaneously to both components. Previous studies by indirect immunofluorescence staining have shown that both UT-II and T-II, the binding component of C2T, bind to isolated epithelial cells and to brush borders of mouse intestine, while component I, the active component of the toxin, binds to cells and brush borders only in the presence of T-II (6). In these experiments, these findings were confirmed with two directly fluorescence-labeled components of C2T in tissue culture cells, and the difference in the dynamic processes of components I and II after binding to the cells was visualized.…”
Section: ) This Indicates That Component I Binds To Cells Bound With mentioning
confidence: 96%
“…These two molecules are functionally different proteins: component II is a binding subunit, and component I is an ADP-ribosyltransferase whose substrate is cytoplasmic actin (7,11). The toxin has various biological activities, lethality, enterotoxicity, and cytotoxicity, all of which are activated by trypsinization of a mixture of the two components and elicited by their cooperation (5,6). These activities of C2T are caused by ADPribosylation of cytoplasmic actin by component I (11).…”
mentioning
confidence: 99%